(The reality of organizational values in Mosul University - a field study from the viewpoint of the teachers) - Tariq Abdel Fattah, Dalia (Journal of College of Education, 2020)
The topic of the research revolves around organizational values ​​as a vital and important matter in institutions, as values ​​are the deepest level in organizational culture, because they have a great role in shaping and directing the behavior of working individuals, they represent the identity of the institution or organization, therefore knowledge of organizational values ​​has a great importance in the success of a work Any institution, including the university institution, and the research aims to take note of the subject of organizational values ​​and know its impact on the work of the institution and identify the prevailing values ​​in the university and determine the most important organizational values ​​within the university, and the research adopted the social survey as it included a sample of (50) teachers from the University of Mosul and distributed questionnaires for this purpose and the research reached the most important results: The research found that (66%) of the sample have an interest in the value of discipline as it is considered one of the most important organizational values ​​for the university institution. The results of the research indicated that there is an interest in teamwork and cooperation within the university, and it is an important value. The research indicated that (84%) of the sample seek to apply law and order within the university.